Pedagogical intervention strategies: Reading as a starting point for literacy - Souza, Dayane Felix; Romão, Adriana; Lima, Eslaine Cardoso de; Schaedler, Karoline; Almeida, Marli Rodrigues de; Scardua, Marta Santana de Pinho (Seven Editora, 2023)
The present work presents the experience report of the intervention project involving reading in classes of 2nd years of elementary school in the State School "Serra Azul" in the municipality of Diamantino - MT in the year 2019. For the execution of the project was thought in differentiated methodologies and strategies that were to meet the educational needs of the children in the respective classes. The goal is that the child can develop a taste for the practice of reading and consequently improve their perception in the process of literacy. As a result of the intervention project it was possible to observe greater interest and participation in class and extra-class activities, as well as better fluency of students who already mastered reading and evolution in the understanding of the alphabetic system in children who are being literate. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-078